Foliar application of calcium, silicon, and potassium nanoparticles improves growth, and fruit quality of drought-stressed cucumber plants through modulation of osmolytes, antioxidant enzymes, photosynthesis efficiency, and phytohormones - Mohamed EL-MOGY; Emad A. ABDELDAYM; Suzy M. ABDELAZIZ; Ahmed Mahmoud ISMAIL; Hossam S. EL-BELTAGI; Khaled M.A. RAMADAN; Abdel Wahab M. MAHMOUD; Shady Abdel MOTTALEB (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2025)
A field experiment was conducted to evaluate the effects of calcium (Ca), potassium (K), and silicon (Si) nanoparticles on growth and production under water stress conditions. The combined application of Ca, K, and Si significantly improved the growth of drought-stressed cucumber plants compared to untreated plants. All nanoparticles similarly enhanced total chlorophyll levels, chlorophyll fluorescence (Fv/Fm), photosynthetic rates, and water use efficiency, as well as the accumulation of indole-acetic acid (IAA) and essential nutrients [magnesium (Mg), potassium (K), calcium (Ca), phosphorus (P), and nitrogen (N)] in the leaves of drought-stressed cucumber plants. The foliar application of combined K, Ca, and Si nanoparticles increased the activity of antioxidant enzymes, alleviating drought stress and scavenging reactive oxygen species (ROS). In contrast, the combined application of Ca, K, and Si nanoparticles resulted in a significant reduction in malondialdehyde (MDA) and abscisic acid (ABA) levels compared to the control treatment. Furthermore, the use of K, Ca, and Si nanoparticles, either alone or in combination, notably improved total yield and its components, including fruit weight and the number of fruits. Compared to untreated plants, the combined application of Ca, K, and Si nanoparticles also increased carbohydrates, total soluble solids, ascorbic acid, and total phenol content, while reducing cucurbitacin content.